EXPLORING THE USEFULNESS OF RICH MATHEMATICAL TASKS TO ENHANCE STUDENTS’ REFLECTIVE THINKING - Fitriati Fitriati; Rita Novita; Rahmah Johar (LPMPP Universitas Negeri Yogyakarta, 2020)
Promoting reflective thinking in daily teaching practice is vital to prepare students to live in a more challenging world. Rich tasks are one of the promising tasks that could be used as pedagogy trend to develop students' reflective thinking. Therefore, the purpose of this study is to describe the usefulness of rich mathematical tasks including how teachers use them in their teaching practice and the improvement of students’ reflective thinking following the rich tasks based instruction. This study employed a teaching experiment within a case study design. Participants were 28 Year 7 students of one the junior high school in Aceh, Indonesia. The instrument of the study is three valid and reliable rich mathematical tasks administered to the students through student worksheet. The results of the study show that rich tasks provided students with the opportunity to solve real-world problems by questioning their understanding and thinking reflectively. It also found that most students in the classroom were able to achieve the low level of reflective thinking with classroom mean score is 60. This value fairly enough since reflective thinking is a complicated concept. Subsequently, the results indicate the rich mathematical tasks approach hold potential in enhancing students’ reflective thinking ability.